Primary spontaneous pneumothorax in a recreational athlete - Van der Colff, F J (South African Journal of Sports Medicine, 2015)
Primary spontaneous pneumothorax (PSP) is relatively uncommon in the athletic population. Because of the subtle nature of the symptoms, the diagnosis is easily missed, which can lead to unnecessary prolonged discomfort and recovery time for the athlete. ere is currently a lack of evidence in the literature concerning treatment and return-to-play protocols referring specically to PSP within the athletic community. is case report highlights the predisposing and important factors in the history of a 34-year-old recreational male athlete who developed PSP. According to the knowledge of the authors, this report of PSP in a recreational athlete is the rst of its kind described in South Africa. Owing to the possibility of life-threatening complications, it is important for sports physicians to be familiar with the important points in the history and to be made aware of the predisposing factors that may lead to PSP.